2009
DOI: 10.1523/jneurosci.2575-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Common Representation of Decision Values for Dissimilar Goods in Human Ventromedial Prefrontal Cortex

Abstract: To make economic choices between goods, the brain needs to compute representations of their values. A great deal of research has been performed to determine the neural correlates of value representations in the human brain. However, it is still unknown whether there exists a region of the brain that commonly encodes decision values for different types of goods, or if, in contrast, the values of different types of goods are represented in distinct brain regions. We addressed this question by scanning subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
441
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(505 citation statements)
references
References 27 publications
60
441
2
2
Order By: Relevance
“…3a). The SEM was based on known anatomical connections between the OFC and NACC and their relationships to subjective likability and purchase decisions (Chib, Rangel, Shimojo, & O'Doherty, 2009;Knutson, et al, 2007;Montague & Berns, 2002;O'Doherty, Kringelbach, Rolls, Hornak, & Andrews, 2001;Plassmann et al, 2007;Rolls, 2000). Consistent with this literature, the average song likability had significant path coefficients to both the OFC and NACC, and because of the direct connection between OFC and NACC, this path was also significant.…”
Section: Resultsmentioning
confidence: 63%
“…3a). The SEM was based on known anatomical connections between the OFC and NACC and their relationships to subjective likability and purchase decisions (Chib, Rangel, Shimojo, & O'Doherty, 2009;Knutson, et al, 2007;Montague & Berns, 2002;O'Doherty, Kringelbach, Rolls, Hornak, & Andrews, 2001;Plassmann et al, 2007;Rolls, 2000). Consistent with this literature, the average song likability had significant path coefficients to both the OFC and NACC, and because of the direct connection between OFC and NACC, this path was also significant.…”
Section: Resultsmentioning
confidence: 63%
“…Previous studies reported that value signals are represented in higher-level cortical regions, such as the medial prefrontal cortex (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Crucially, however, those studies did not answer the question of whether these regions play an active role in computing these signals or whether they merely represent the consequence of the decision.…”
Section: Resultsmentioning
confidence: 96%
“…Despite previous reports implicating the medial prefrontal cortex in encoding expected value signals (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), it remained unclear whether this region is directly involved in computing value, because these signals are often thought to reflect the consequence of the decision process instead (in the sense that value can only be encoded once a decision has been made). In this work, we provide a mechanistic account that directly implicates the medial prefrontal cortex in value computation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the mOFC might comprise a common valuation region that encodes for both appetitive and aversive DVs (Litt et al 2011). These results and related ones using monetary gambles and trinkets (Chib et al 2009), or immediate and delayed rewards Glimcher 2007, 2010) provide evidence that the brain encodes a "common currency" that allows for a shared valuation for different categories of goods (see Kable and Glimcher 2009, for a review).…”
Section: Understanding Value and Its Computationmentioning
confidence: 58%